The Life Events of Adolescents: Implications for Rural School Nurses - Kathryn R Puskar; Beth R Grabiak; Dianxu Ren (Rural Nurse Organization; Binghamton University, 2011)
The purpose of this study was to describe life events of rural adolescents and their relationship to depression. The design was a cross sectional survey. The sample included 193 students attending three rural high schools in southwestern Pennsylvania. Measures included The Life Events Checklist and The Reynolds Adolescent Depression Scale (RADS-2). Results showed that the mean number of life events was eighteen. Females reported more life events and more negative life events than males. There was a moderate, linear correlation between negative life events and depression (r = .361; p < 0.0001). Rural school nurses should include adolescents' recent life events in the health history. Awareness of negative life events as a precipitating factor in depression constitutes appropriate screening and referral by rural school nurses.